(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2009)
Indonesia has 1.5 million hectare of cocoa plantation in 2008. which hasstrategic position in carbon dioxide absorption to decrease global warming. Biomass approach method in plants carbon stock estimation specific for cocoa is still not available. The aim of this research is to determine carbon stock in 1—30 years ages of cocoa plants and to measure carbon stock in various cocoa planting systems using specific allometric formula of carbon stock estimation. Regression model on plant biomass estimation was estimated based on height, diameter, and their combination. Carbon stock estimation in different ages and plan tation system of cocoa was conducted by randomized completely block design with 3 replications. The result showed that model Y:áDâ as the best allometric formula, where Y is plant biomass, D is diameter at the breast hight, â is a constant with a value of 0.1208 and á was a constant of 1.98. Increasing of carbon stock in cocoa plantations was proportional to the ages of the plants according to the polinomial equation Y=0.0518X2+2.8976X–4.524. Agroforestry system increased carbon stock in cocoa plantation. Cocoa-Paraserianthes falcataria plantation system produce highest of carbon stock in 7 years. Key words : Carbon stock, allometric, cocoa, ages of plant, planting system.